Experimental studies on bagasse ash reinforced with GF and BF-slag in direction towards sustainable development - Harshal Ramesh Nikhade; Anshul Ramesh Nikhade; Shital Telrandhe; Nitin K Mandavgade; Bhushan Yograj Hatwar (Institute of Advanced Engineering and Science, 2024)
To assess the appropriateness of the current by-product for application in building construction and to mitigate potential environmental risks in the context of environmental sustainability, a series of tests were conducted to determine the compressive strength properties of a material composed of glass fiber (GF) strengthened sugar cane bagasse ash (SCA). This material was made from SCA, blast furnace slag (BF-slag), and GF binding with cement. Cylinders were employed to measure the compressive strength of a mixture consisting of water and an SCA ratio of 50%. Cylindrical samples of 150 millimeters in length and 75 millimeters in diameter were utilized to evaluate the compressive strength across curing durations of 7, 14, and 28 days. The present study attempt utilizes mixture ratio percent of 0.15, 0.3, 0.45, 0.6, and 0.75 to perform compressive strength tests. The compressive strength of cylindrical samples ranges from 86.5-801.6 kPa. The density of a cylindrical sample containing 30% cement dropped from 900.1-865 kg/m3. The initial tangent stiffness of the sample ranges from 66-630 MPa. The findings suggest that it is possible to achieve a material with acceptable strength by using SCA ash in combination with BF-slag, strengthened with GF.